2004
DOI: 10.1162/0898929041502751
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Evidence for Separable and Lateralized Prefrontal Memory Monitoring Processes

Abstract: Source memory research suggests that attempting to remember specific contextual aspects surrounding prior stimulus encounters results in greater left prefrontal cortex (PFC) activity than simple item-based old/new recognition judgments. Here, we tested a complementary hypothesis that predicts increases in the right PFC with tasks requiring close monitoring of item familiarity. More specifically, we compared a judgment of frequency (JOF) task to an item memory task, in which the former required estimating the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
65
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 43 publications
12
65
1
1
Order By: Relevance
“…Given that there were several cognitive control processes that were not directly manipulated in the current experiment, it is possible that right DLPFC activity in this study may be related to any of these control processes. However, our current results are consistent with previous studies implicating right DLPFC in monitoring processes engaged during familiarity-related retrieval processing (Dobbins, Simons, & Schacter, 2004;Dudukovic & Wagner, 2007;Henson, Rugg, Shallice, & Dolan, 2000;Petrides, 2000b) …”
Section: Retrieval-related Activity In Right Dlpfcsupporting
confidence: 93%
See 1 more Smart Citation
“…Given that there were several cognitive control processes that were not directly manipulated in the current experiment, it is possible that right DLPFC activity in this study may be related to any of these control processes. However, our current results are consistent with previous studies implicating right DLPFC in monitoring processes engaged during familiarity-related retrieval processing (Dobbins, Simons, & Schacter, 2004;Dudukovic & Wagner, 2007;Henson, Rugg, Shallice, & Dolan, 2000;Petrides, 2000b) …”
Section: Retrieval-related Activity In Right Dlpfcsupporting
confidence: 93%
“…It has been argued that increased right DLPFC activity during both EM and WM recency tasks reflects the role of this region in familiarity-based retrieval monitoring (Dobbins, Rice, Wagner, & Schacter, 2003;Dobbins, Simons, & Schacter, 2004;Mitchell, Johnson, Raye, & Greene, 2004;Yonelinas, Otten, Shaw, & Rugg, 2005). According to this perspective recognition and temporal context retrieval tasks can be performed by making judgments about the relative feelings-of-familiarity of retrieved stimuli, wherein more recent stimuli are inherently more salient and thus more familiar.…”
Section: Retrieval-related Activity In Right Dlpfcmentioning
confidence: 99%
“…Recent findings from neuroimaging studies have supported the idea that the left and right PFC may contribute differently to recollection and familiarity processes (Nolde et al, 1998;Cabeza et al, 2003;Kensinger et al, 2003;Dobbins et al, 2004;Mitchell et al, 2004) (for review, see Ranganath, 2004). For example, some researchers have suggested that the left PFC might disproportionately contribute to recollection of specific information (Nolde et al, 1998;Kensinger et al, 2003;Dobbins et al, 2004;Mitchell et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Because stimulus presentation was lateralized during encoding, we were able to assess memory performance separately for objects processed preferentially by the lesioned versus the spared hemisphere. In addition, prompted by neuroimaging evidence suggesting that there may be some laterality differences within the PFC in regard to recollection and familiarity (Nolde et al, 1998;Kensinger et al, 2003;Dobbins et al, 2004;Mitchell et al, 2004), we characterized the effects of left versus right frontal lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is thought to play a critical role in the storage and/or recollection of contextual associations (43). In contrast, activation specifically of right-lateralized frontal and parietal regions has been associated with controlled memory retrieval (44) and heuristic evaluation processes (45), the monitoring of retrieved memoranda (46), and more general retrieval-related decision-making (47). Together, these findings indicate that the DMN supports rapid, effortless retrieval of contextual associations, whereas the RFPN may support more strategic searches through memory and/or the monitoring of retrieved information.…”
Section: Discussionmentioning
confidence: 99%